Pilihan Pengobatan pada Pasien Psoriasis dengan HIV: Sebuah Tinjauan Sistematik - Helmina Robiyatul Umami (Jurnal Sains & Kesehatan, 2023)
Psoriasis is a disease related to the immunity, usually inherited genetically and is chronic and recurring. When patients with psoriasis are infected with the Human Immunodeficiency Virus (HIV), the theory is that there is a paradoxical relationship that affects the two diseases. HIV can be a trigger for psoriasis and psoriasis can appear as an early symptom of HIV infection. The successful treatment of Psoriasis with HIV positive must be done appropriately according to the patient's condition. Here we discuss several Psoriasis therapy options in HIV positive patients based on several case reports that have a variety of different diseases. The research design is a literature review and refers to the PRISMA method. Scientific articles searchable on PubMed. There were 13 scientific articles related to Psoriasis patients who were HIV positive and met the inclusion criteria. Initial treatment of Psoriasis using biological therapy such as Risankizumab and Secukimab 300 mg subcutaneously, can change the response rate of the Psoriasis Area and Severity Index to 100 or the total loss of psoriasis lesions after a few weeks. In addition, the treatment of psoriasis together with High-active antiretroviral therapy (HAART) also affects the improvement of Psoriasis.